Condições de trabalho e de saúde: análise de diferenciais de gênero - Cordeiro, Samara Bruno Moura (2011)
Neoliberalism and restructuring caused to several changes in the labor market that resulted in precarious conditions. The profile of the job characteristics and its impact on the health of workers has proven quite different between genders. The study aimed to analyse gender differences in relation to sociodemographic and work characteristics of residents in urban areas of Feira de Santana, Bahia; describe characteristics of working life and psychosocial characteristics of domestic work, by gender, to estimate the prevalence of self-reported health problems, common mental disorders - CMD and alcoholism in the population of Feira de Santana - BA, according to gender and to evaluate the association between work characteristics and major health problems of workers in Feira de Santana, considering gender differences. This is an epidemiological cross-sectional, descriptive, conducted in year 2007-2008. The field of study was the urban city of Feira de Santana. Data were collected using a questionnaire, applied to the selected households eligible residents (aged ≥ 15 years) by trained interviewers. We studied 4170 people over 15 years, 2,819 females and 1,351 males. Of this total, 1,557 were working at the time of the survey, 851 women and 706 men. Used variables concerning working conditions, variables related to health, and sociodemographic. The variables were stored in a database generated by SPSS (Statistical Package for the Social Sciences) version 10.0. Will be held to select the variables of interest and possibly the creation of other relevant variables, use will also Epi-Info 6.0 program and R. The study was approved by the Ethics in Research of Universidade Estadual de Feira de Santana, through the opinion No. 241/2006. We found a reduced participation of women in the labor market and a trend of increasing precariousness of women's work, with activities of lower status, lower pay, greater vulnerability, job insecurity, predominance of informal jobs and subordination. In addressing the psychosocial characteristics, women continued to be subjected to the worst conditions in the workplace, with low control. The high strain at work was higher among women. This establishes a situation of stress that promotes physical and mental ailment of the body. The health situation was more aggravating for women was higher prevalence for all self-reported health problems and mental disorders, except for alcoholism was higher among men. The results are discussed considering the possible association of health status with the overload of activities of women relative to men, since it was shown that women are mainly responsible for household chores.